Neural Oscillatory and Network Mechanisms of Uncertainty Processing in Adolescent Anxiety: A Narrative Review - Zhao, Cheng; Song, Jinling; Wang, He; Gao , Yinan; Liu, Yingjie; Chen , Yunen (Scientific Journal of Technology, 2026)
Adolescence represents a sensitive developmental period characterized by profound neurobiological maturation and increased vulnerability to anxiety disorders. Among the cognitive domains influenced by anxiety during this stage, uncertainty processing occupies a central position. Uncertainty arises when environmental outcomes are ambiguous, unpredictable, or probabilistic, requiring integration of cognitive control, emotional regulation, reward evaluation, and attentional allocation. Converging evidence suggests that adolescents with elevated anxiety exhibit heightened sensitivity to potential threat, reduced tolerance of ambiguity, and altered neural responses during uncertain situations.Electroencephalography (EEG) has emerged as a powerful method for investigating the temporal dynamics of neural oscillations underlying uncertainty processing. Frequency-specific oscillatory activity in the theta, alpha, and beta bands has been linked to cognitive control, vigilance, and top-down regulatory processes. In addition, functional connectivity analyses reveal large-scale network coordination patterns that shape adaptive responses to uncertainty. Alterations in oscillatory power and phase synchronization may reflect dysregulated interaction between prefrontal control systems and emotion-related circuits in anxious youth.This narrative review synthesizes current developmental and electrophysiological research on neural oscillations and network mechanisms associated with uncertainty processing in adolescent anxiety. By integrating findings across cognitive neuroscience and developmental psychopathology, this review aims to clarify potential neural pathways underlying anxiety-related biases and to outline directions for future investigation.